183k views
3 votes
NEED HELP FAST!!!!!!!!!

NEED HELP FAST!!!!!!!!!-example-1

2 Answers

4 votes

h= k/j

Multiply by j for the left and right hand side

(h)(j)= k/j(j)

Cross out j and j for the right hand side.

hj= k

answer is : k= hj

I think this is the answer

User Aillyn
by
5.4k points
4 votes

ANSWER


k = hj

Step-by-step explanation

The given formula is:


h = (k)/(j)

We want to solve this formula for k.

Let us multiply both sides by j.


h * j = (k)/(j) * j

Cancel the common factors.


hj = k

Or we rewrite to obtain,


k = hj

k is now isolated on one side of the equation.

User FredFlinstone
by
5.7k points